Hybrydowa pamięć architektoniczna w grach wideo. Między doświadczeniem realnym a wirtualnym - Kiecko, Emilia (Artium Quaestiones, 2025)
This article examines the complex relationship between architecture in video games and memory, which shapes how it is experienced and interpreted. It begins from the premise that video games generate and employ a distinctive form of spatial memory, one that combines encounters with real architecture, media conventions, and cultural expectations tied to particular types of spaces. This hybrid form of memory functions as a kind of palimpsest, layering real and virtual experiences. Scholars have proposed various theoretical frameworks for understanding architecture in games: Espen Aarseth regarded it as an allegory of real space; Celia Pearce as the art of designing experiences; Christopher Totten as a functional analogue of actual architecture; Gabriele Aroni as a complex iconic sign or a “digital capriccio”; and Henry Jenkins, above all, as a narrative tool. Despite their differences, these perspectives converge on the assumption that a shared mechanism of memory underlies the operation of architecture in games. The analysis also draws on several key concepts of memory. Henri Bergson’s idea of the bodily rootedness of perception, developed further by Juhani Pallasmaa, explains the paradox of experiencing immaterial architecture as real. Kaja Silverman’s notion of the “remembering look” sheds light on how players reinterpret virtual spaces. Alison Landsberg’s concept of “prosthetic memory” clarifies how media produce memories of places and events never personally encountered, while Astrid Erll’s idea of “transcultural memory” illuminates the circulation of architectural memory across global cultural contexts. A central case study is the reconstruction of Notre-Dame Cathedral in Assassin’s Creed: Unity (Ubisoft Montréal, 2014). The virtual model of the monument, while distinguished by impressive attention to detail and extensive use of historical sources, also incorporates deliberate anachronisms. These design choices stemmed from a multilayered strategy in which the aim was less historical fidelity than the evocation of spatial sensations approximating the experience of the actual building, as well as an appeal to contemporary imaginings of the cathedral. Such anachronisms can be interpreter through Georges Didi-Huberman’s concept of anachronism, which holds that every act of memory is by definition anachronistic. This framework helps explain why the game’s version of Notre-Dame was perceived by players as so “authentic.” Following the fire at the actual cathedral in 2019, rumours circulated that the game’s model might be used in its reconstruction. Although repeatedly denied, these speculations were not entirely dispelled. Their persistence testifies to the success of the visual strategy employed by the game’s designers: despite numerous anachronisms and conscious deviations from historical accuracy, they created a virtual cathedra that for many audiences became as “real” as the original. This case of virtual spaces infiltrating collective memory and imagination represents, to date, perhaps the most striking consequence of the hybrid memory shaped by video games.